Réponses

Meilleure réponse !
2014-09-20T14:11:27+02:00
A = (3/2)² - 1/3 x (- 5/2)
A = 3²/2² + 5/6
A = 9/4 + 5/6
A = 9 x 6 / 4 x 6 + 5 x 4 / 6 x 4
A = 54/24 + 20/24
A = 74/24
A = 2 x 37 / 2 x 12
A = 37/12

B = 11/3 - 7
        25/6
B = 11/3 - 7 x 3 / 1 x 3
               25/6
B = 11/3 - 21/3
           25/6
B = - 10/3 : 25/6
B = - 10/3 x 6/25
B = - 60/75
B = 15 x - 4 / 15 x 5
B = - 4/5

C = 1 - 1/3 x 3/4 - 1/5
         3
C = 1 x 3  / 1 x 3 - 1/3 x 3/4 - 1/5
                  3
C = 3/3 - 1/3  x 3/7 - 1/5
          3
C = 2/3 x 3/7 - 1/5
       3
C = 2/3 : 3 x 3/7 - 1/5
C = 2/3 x 1/3 x 3/7 - 1/5
C = 2/9 x 3/7 - 1/5
C = 6/63 - 1/5
C = 6 x 5 / 63 x 5 - 1 x 63 / 5 x 63
C = 30/315 - 63/315
C = - 33/315
C = 3 x - 11 / 3 x 105
C = - 11/105

D = 6 - 4 (1/4 - 1)²
D = 6 - 4 (1/4 - 1 x 4 / 1 x 4)²
D = 6 - 4 (1/4 - 4/4)²
D = 6 - 4 (1²/4² - 4²/4²)
D = 6 - 4 (1/16 - 16/16)
D = 6 - 4 (- 15/16)
D = 6 + 60/16
D = 6 x 16 / 1 x 16 + 60/16
D = 96/16 + 60/16
D = 156/16
D = 4 x 39 / 4 x 4
D = 39/4

E = 4/3 - 1/3 : (3 + 1/2)
E = 4/3 - 1/3 : (3 x 2 / 1 x 2 + 1/2)
E = 4/3 - 1/3 : (6/2 + 1/2)
E = 4/3 - 1/3 : 7/2
E = 4/3 - 1/3 x 2/7
E = 4/3 - 2/21
E = 4 x 7 / 3 x 7 - 2/21
E = 28/21 - 2/21
E = 26/21

J ZFQZDQQDZDZAAazzf
Oups, Merci beaucoup !!